The modification of microstructure to improve the biodegradation and mechanical properties of a biodegradable Mg alloy - Han, Hyung-Seop; Minghui, Yin; Seok, Hyun-Kwang; Byun, Ji-Young; Cha, Pil-Ryung; Yang, Seok-Jo; Kim, Yu Chan (ELSEVIER SCIENCE BV, 2013)
The effect of microstructural modification on the degradation behavior and mechanical properties of Mg-5 wt%Ca alloy was investigated to tailor the load bearing orthopedic biodegradable implant material. The eutectic Mg/Mg2Ca phase precipitated in the as-cast Mg-5 wt%Ca alloy generated a well-connected network of Mg2Ca, which caused drastic corrosion due to a micro galvanic cell formed by its low corrosion potential. Breaking the network structure using an extrusion process remarkably retarded the degradation rate of the extruded Mg-5 wt%Ca alloy, which demonstrates that the biocompatibility and mechanical properties of Mg alloys can be enhanced through modification of their microstructure. The results from the in vitro and in vivo study suggest that the tailored microstructure by extrusion impede the deterioration in strength that arises due to the dynamic degradation behavior in body solution. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: IN-VIVO CORROSION; MAGNESIUM ALLOYS; IMPLANTS; BIOMATERIALS; BONE; CA